2002
DOI: 10.1161/hs0202.102732
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Increases Rat Cerebrovascular Prostacyclin Synthesis by Elevating Cyclooxygenase-1 and Prostacyclin Synthase

Abstract: Background and Purpose-It has been reported that estrogens modulate peripheral vascular synthesis of vasodilatory hormones, including prostacyclin. If this occurs in the cerebral circulation, it could have important consequences in the modulation of cerebral hemodynamic function and improvement of stroke outcome. We investigated the hypothesis that in vivo 17␤-estradiol treatment of ovariectomized rats increases cerebrovascular prostacyclin production via elevation of the enzymes responsible for prostacyclin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 56 publications
6
102
1
Order By: Relevance
“…Increased levels of PGI 2 upon stimulation with estradiol have been associated with increased expression of the key enzymes involved in PGI 2 production, phospholipase A 2 , COX-1, and prostacyclin synthetase (PGIS), as demonstrated in rat cerebral blood vessels, where chronic in vivo 17ß-estradiol treatment enhances basal PGI 2 synthesis by increasing COX-1 and PGIS proteins (27). It seems that the COX-2 pathway also plays a specific role in estradiol-induced PGI 2 synthesis and vasodilation.…”
Section: Arachidonic Acid Metabolitesmentioning
confidence: 99%
“…Increased levels of PGI 2 upon stimulation with estradiol have been associated with increased expression of the key enzymes involved in PGI 2 production, phospholipase A 2 , COX-1, and prostacyclin synthetase (PGIS), as demonstrated in rat cerebral blood vessels, where chronic in vivo 17ß-estradiol treatment enhances basal PGI 2 synthesis by increasing COX-1 and PGIS proteins (27). It seems that the COX-2 pathway also plays a specific role in estradiol-induced PGI 2 synthesis and vasodilation.…”
Section: Arachidonic Acid Metabolitesmentioning
confidence: 99%
“…In the vast majority of experiments, cells were exposed to estradiol during 24-48 hours, and the increase of prostacyclin above control values ranged from 16 % to 78 % (Table 1). In addition, it has been shown that estradiol stimulates production of prostaglandins in a variety of preparations of arteries, including ovine uterine arteries (Vagnoni & Magness, 1998;Janowiak et al, 1998;Habermehl et al, 2000), mesenteric arteries from ovariectomized rats (Davidge & Zhang, 1998;Armstrong et al, 2002), rat cerebral blood vessels (Ospina et al, 2002;Ospina et al, 2003), and aorta from ovariectomized monkeys (O'Sullivan et al, 2001). The increase of prostacyclin production is of a similar magnitude to that obtained with cultured endothelial cells.…”
Section: Delayed (Genomic) Effects Of Estrogens On Prostanoids Vasculmentioning
confidence: 67%
“…Prostacyclin increased levels after vessel stimulation with estradiol have been mainly associated with enhanced expression of COX-1. In this way, COX-1 protein content is increased in rat (Ospina et al, 2002) and mice (Geary et al, 2001) cerebral blood vessels, and in ovine uterine arteries in response to treatment with estrogen (Rupnow et al, 2002). Indeed, COX-1 (but not COX-2) expression is increased in the endothelium of the ovine uterine artery during the follicular phase of the ovarian cycle and during pregnancy, where estrogen levels are highest (Janowiak et al, 1998;Habermehl et al, 2000).…”
Section: Delayed (Genomic) Effects Of Estrogens On Prostanoids Vasculmentioning
confidence: 91%
“…As stated, the cardioprotective effects of prostacyclin and of the female hormone estrogen (E2) are well documented [21]. Indeed expression of the prostacyclin receptor (IP) gene, the PTGIR, can be directly regulated by E2 which occurs through a transcriptional mechanism involving direct binding of the estrogen receptor (ER)α to a conserved estrogen response element (ERE) within the promoter region of the PTGIR [23].…”
Section: Effects Of the Androgen Dht On Regulating Ptgir Expressionmentioning
confidence: 99%